Prognostic Significance of Baseline Neutrophil Count and Lactate Dehydrogenase Level in Patients With Esophageal Squamous Cell Cancer Treated With Radiotherapy - Luo, He-San; Xu, Hong-Yao; Du, Ze-Sen; Li, Xu-Yuan; Wu, Sheng-Xi; Huang, He-Cheng; Lin, Lian-Xing (Frontiers in Oncology, 2020)
Background: This present study aimed to explore the prognostic value of pretreatment neutrophil and lactate dehydrogenase (LDH) and develop a prognostic risk scoring model to predict prognosis in esophageal squamous cell cancer (ESCC) patients treated with definitive radiotherapy. Methods: Retrospectively collected data of patients who received definitive radiotherapy for ESCC at Shantou Central Hospital between January 2009 and December 2015 were included for analysis. The association between the level of LDH and neutrophil and clinicopathological characteristics were analyzed. We performed Univariate and multivariate analyses to identify the prognostic predictors for patients with ESCC. Based on the results, we also developed a prognostic risk scoring model and assessed its predictive ability in the subgroups. Results: A total of 567 patients who received definitive radiotherapy for ESCC were included in the present study. The optimal cutoff values were 4.5 *10^9/L, 3.25 and 220 U/L for neutrophil, neutrophil-to-lymphocyte ratio (NLR) and LDH, respectively. A high level of LDH was significantly associated with advanced N stage (p=0.031) and neutrophil count was significantly associated with gender (p=0.001), T stage (p<0.001), N stage (p=0.019), clinical stage (p<0.001) and NLR (p<0.001). Multivariate survival analysis identified gender (p=0.006), T stage (p<0.001), N stage (p=0.008), treatment modality (p<0.001), LDH level (p=0.012) and neutrophil count (p=0.038) as independent prognostic factors for overall survival. Furthermore, a new prognostic risk scoring (PRS) model based on six prognostic factors was developed, could dividing the patients into three groups with distinct prognosis (2= 67.94, p<0.0001). Conclusions: Elevated baseline LDH level and neutrophil count predicted poor prognosis for ESCC patients treated with definitive radiotherapy. A PRS model comprised of LDH, neutrophil count and other prognostic factors would help identify the patients who would benefit most from definitive radiotherapy.